2020
DOI: 10.5937/zembilj2001046m
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the varying intensity light on some morpho-anatomical characteristics and physiological parameters in young plants of Pisum sativum L.

Abstract: In order to determine the extent to which reduced light intensity affects some morpho-anatomical characteristics and physiological parameters in young plants of Pisumsativum L. we compared certain plant parameters grown at full illumination (3200 lux) with plants grown at lower intensity illumination (1700, 1000 and 650 lux) in this research.The ultimate goal is a better understanding of the adaptations of the studied species (variety) to different light treatments. Low light intensity had a negative effect on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…There are no published information by other researches except our earlier studies on the response of the chicory endive to abiotic factors such as temperature, humidity and duration sunny days. However, a large number of studies on the influence of the hydrothermal coefficient and climatic factors on the growth and development of other plants agree that excessive fluctuations in temperature and precipitation have different effects on different phases of plant growth and development (e.g., Zervoudakis et al, 2012;Romanovskaja et al, 2016;Vahabinia et al 2019;Maksimović et al, 2020). So, Maksimović et al (2020) studying the effect of light on morphological and physiological characteristics of peas reported that intensity of transpiration decreased with decreasing illumination due to decrease in the number of stomatal cells.…”
Section: Resultsmentioning
confidence: 99%
“…There are no published information by other researches except our earlier studies on the response of the chicory endive to abiotic factors such as temperature, humidity and duration sunny days. However, a large number of studies on the influence of the hydrothermal coefficient and climatic factors on the growth and development of other plants agree that excessive fluctuations in temperature and precipitation have different effects on different phases of plant growth and development (e.g., Zervoudakis et al, 2012;Romanovskaja et al, 2016;Vahabinia et al 2019;Maksimović et al, 2020). So, Maksimović et al (2020) studying the effect of light on morphological and physiological characteristics of peas reported that intensity of transpiration decreased with decreasing illumination due to decrease in the number of stomatal cells.…”
Section: Resultsmentioning
confidence: 99%